Assessment of ethanol exposure from hand sanitizer use and potential for developmental toxicity in nursing infants. Issue 9 (2nd February 2022) - Han, Alice A.; Buerger, Amanda N.; Allen, Hannah; Vincent, Melissa; Thornton, Stephanie A.; Unice, Kenneth M.; Maier, Andrew; Quiñones‐Rivera, Antonio
Abstract: Ingestion of ethanol during pregnancy is known to have detrimental effects on the fetus. Although the potential developmental effects of maternal ethanol intake during lactation are less well characterized, public health guidelines recommend avoidance of alcohol or, if alcohol is consumed, to allow for 1–2 h to pass before nursing. A proposal to classify ethanol as potentially harmful to breast‐fed children warrants an investigation of the potential adverse neurodevelopmental effects of low‐dose ethanol exposure during lactation. There currently are no studies that have examined neurodevelopmental outcomes from lactational exposure to ethanol from the use of topical products that contain ethanol, such as alcohol‐based hand sanitizers (ABHS). Furthermore, the epidemiological literature of lactational ethanol exposures from maternal alcohol consumption is limited in design, provides equivocal evidence of neurological effects in infants, and is insufficient to characterize a dose–response relationship for developmental effects. Toxicological studies that observed neurodevelopmental effects in pups from ethanol via lactation did so at exceedingly high doses that also caused maternal toxicity. In this investigation, blood ethanol concentrations (BECs) of breastfeeding women following typical‐to‐intense ABHS use were computationally predicted and compared to health benchmarks to quantify the risk for developmental outcomes. Margins of 2.2 to 1000 exist between BECs associated with ABHS use compared to BECs associated with neurotoxicity adverse effect levels in the toxicology literature or oral ethanol intake per public health guidelines. Neurodevelopmental effects are not likely to occur in infants due to ABHS use by breastfeeding women, even when ABHSs are used at intense frequencies. Abstract : Adverse neurodevelopmental effects of ethanol exposure are supported by toxicological studies; ethanol as a potential "lactation hazard" needs evaluation. A lactation hazard may not be applicable for all ethanol‐containing products, such as hand sanitizers. Furthermore, internal dose assessments of hand sanitizer use are lacking. Computationally modeled blood ethanol concentrations following hand sanitizer use are lower than concentrations associated with toxicological and guideline benchmarks. Therefore, there is low potential for the use of ethanol‐containing hand sanitizers to be a lactation hazard.